(untitled) (Circe de clásicos y modernos, 2017)
This paper offers expects to present a Spanish translation (apparently nonexistent) of the Amicitia exulans, a 12th century dramatic piece; and to offer same textual variants, notes and a study that hopes to characterize it, inside the dramatic genre, as a “Byzantine allegoric tragedy”, with typical features and as suitable for a real performance.